If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2n + -4(n + 8) = 4n + -12 Reorder the terms: -2n + -4(8 + n) = 4n + -12 -2n + (8 * -4 + n * -4) = 4n + -12 -2n + (-32 + -4n) = 4n + -12 Reorder the terms: -32 + -2n + -4n = 4n + -12 Combine like terms: -2n + -4n = -6n -32 + -6n = 4n + -12 Reorder the terms: -32 + -6n = -12 + 4n Solving -32 + -6n = -12 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. -32 + -6n + -4n = -12 + 4n + -4n Combine like terms: -6n + -4n = -10n -32 + -10n = -12 + 4n + -4n Combine like terms: 4n + -4n = 0 -32 + -10n = -12 + 0 -32 + -10n = -12 Add '32' to each side of the equation. -32 + 32 + -10n = -12 + 32 Combine like terms: -32 + 32 = 0 0 + -10n = -12 + 32 -10n = -12 + 32 Combine like terms: -12 + 32 = 20 -10n = 20 Divide each side by '-10'. n = -2 Simplifying n = -2
| 2x^2+75=0 | | -144=4x^4-64x^3+254x^2-2x | | 90+c=19 | | 2x/6-4x+8/4=7 | | 7+u=-69 | | 2y+3x-12=0 | | y-(-7)=(-5/6)(x-7) | | -71+u=11 | | 6y-3=9y | | 5(P-8)=P+3 | | -8(x+6)=6v-34 | | (-5/6)(x-7) | | w-69=-63 | | 4x+80=50x-12 | | 7=32+b | | -19-6k=6(1+3k) | | 2,3f+12=40 | | 6x^9/x^2 | | 17x-3=9x+13 | | 49x^2-56+16= | | 3t^2-24t+45=0 | | 4p+12= | | (N+4)*3=36 | | 6x+2=3x+7 | | A/6-1=7 | | 11=r/13 | | x/5=4/16 | | 2x+6=3x-9 | | 3x+5=55-9x | | 3x-6.8=31 | | 7d-12=38 | | 125-6x=30x+21 |